Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Ibu Hamil Primigravida Trimester III Dalam Menghadapi Persalinan - Diani Octaviyanti Handajani (IJMT : Indonesian Journal of Midwifery Today, 2021)
During pregnancy, the mother will experience changes in physical and emotional conditions, which are the main factors for pregnant women, especially primigravida pregnant women. Changes that occur if not handled properly will cause anxiety. Support from the family is needed to deal with the anxiety problems of pregnant women in facing childbirth. This study aims to determine whether there is a relationship between family support and anxiety levels in third trimester primigravida pregnant women who will face childbirth. This research is an analytic observational study with cross sectional approach, with a sample of 30 mothers. The study was conducted at PMB Murtini Surabaya. The data called by quissioner and it was analytical with correlation rank spearman by using SPSS application with α=0,05. The results of this study indicate that there is a relationship between family support and anxiety levels in third trimester primigravida pregnant women who are facing labor with the results of rank spearman correlation is p = 0.001. Postive family support is very important to reduce the level of maternal anxiety in dealing with childbirth.